MUSLIMAH AESTHETIC EDUCATION AS AN INTEGRATED LEARNING STRATEGY FOR SECONDARY LEVEL FEMALE STUDENTS IN THE ERA OF THE DEATH OF EXPERTISE - Feryani, Elsa; Handrianto, Budi; Syafrin, Nirwan (Edukasi Islami: Jurnal Pendidikan Islam, 2025)
Background: The era of the "death of expertise," characterized by an overwhelming flow of unverified digital information, poses a threat to the critical reasoning ability (bashirah) of students, particularly among females. Purpose: This study aims to design, implement, and evaluate an integrated Islamic Aesthetic Education model as a pedagogical strategy to enhance aesthetic sensitivity (dzauq) and critical thinking among female students in a modern Islamic boarding school. The model synthesizes Dewey's theory of experience with the concept of ihsan, emphasizing experiential and reflective learning. Method: Using a Participatory Action Research (PAR) design, the study actively involves students in each learning cycle. Findings reveal that the model significantly improves students’ aesthetic sensitivity and critical reasoning, thereby strengthening their character. Result: This highlights the role of aesthetic education as an antidote to superficial information, equipping students to engage with content more thoughtfully and critically. Additionally, the model fosters the development of moral awareness, empathy, and social responsibility. These results underscore the importance of an education approach that not only focuses on information mastery but also on character-building and critical thinking, grounded in ihsan and meaningful experiences. Conclusion: Consequently, this model offers valuable insights for broader implementation in Islamic educational institutions, addressing similar challenges in today’s digital age.